Blood pressure reduction and control with fixed-dose combination perindopril/amlodipine: A Pan-Hellenic prospective observational study. (December 2015) - Manolis, Athanasios; Grammatikou, Violetta; Kallistratos, Manolis; Zarifis, John; Tsioufis, Konstantinos
Introduction: Hypertension guidelines recommend fixed-dose combinations for enhanced blood pressure (BP) reduction and compliance. The objective of this study was to assess the effectiveness and safety of fixed-dose perindopril/amlodipine combination in reducing and controlling BP in Greek hypertensive patients, as well as the effect of baseline BP and added cardiovascular risk on BP reduction. Methods: This 6-month prospective observational study included male or female patients ⩾18 years with essential hypertension prescribed fixed-dose combination perindopril/amlodipine. BP was measured at baseline and 3 and 6 months. Baseline cardiovascular risk and treatment compliance were also assessed. Results: In 2231 per protocol patients, mean systolic BP decreased from 157.0±15.4 mm Hg to 129.0±7.9 mm Hg after 6 months, and diastolic BP from 91.5±10.1 to 78.8±6.7 mm Hg (both p < 0.001). BP control was achieved in 84.8% at 6 months. Patients with higher baseline added cardiovascular risk or BP had greater BP reduction ( p < 0.001). Compliance was good (97.1% took treatment "every day" or "quite often") and few ( n = 27; 1.2%) discontinued treatment prematurely due to adverse events. Conclusions: Fixed-dose perindopril/amlodipine safely and effectively reduced high BP in real-life practice, achieving BP control in most patients. About half of Greek hypertensive patients have high/very high added cardiovascular risk.